1979
DOI: 10.1111/j.1365-3040.1979.tb00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of copper and manganese to the xylem exudate of sunflower

Abstract: Absorption of copper and manganese by sunflower roots from solution cultures of varying composition was followed by measuring the concentrations of the metals appearing in whole roots, root cell sap and xylem exudate. Total copper in the fibrous roots was linearly related to the concentration of copper in the external solution but the concentration of copper released to the xylem exudate was buffered somewhat against the changes made externally. No such buffering was observed for managenese. A copper-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 13 publications
1
18
0
2
Order By: Relevance
“…"Partially mobile" manganese, as defined by Bucovac and Wittwer (1957), is considered to correspond to a cationic Mn 2+ that may account for most of manganese contained in the sampled leaves with brown spots. Such findings are in agreement with observations showing that soluble manganese in ryegrass occurs in a single cationic, perhaps non-complexed form (Bremner and Knight 1970), and that manganese is absorbed mainly as Mn 2+ and translocated predominantly as free divalent cation in the xylem (Graham 1979). Clarkson and Hanson (1980) reported that manganese had the lowest complex stability constant and thus formed the weakest bonds among the micronutrient transition metals such as manganese, iron, copper, zinc, and molybdenum.…”
Section: Resultssupporting
confidence: 90%
“…"Partially mobile" manganese, as defined by Bucovac and Wittwer (1957), is considered to correspond to a cationic Mn 2+ that may account for most of manganese contained in the sampled leaves with brown spots. Such findings are in agreement with observations showing that soluble manganese in ryegrass occurs in a single cationic, perhaps non-complexed form (Bremner and Knight 1970), and that manganese is absorbed mainly as Mn 2+ and translocated predominantly as free divalent cation in the xylem (Graham 1979). Clarkson and Hanson (1980) reported that manganese had the lowest complex stability constant and thus formed the weakest bonds among the micronutrient transition metals such as manganese, iron, copper, zinc, and molybdenum.…”
Section: Resultssupporting
confidence: 90%
“…The essential acidic L-amino acids give greatest enhancement of Cu uptake; once in the blood stream the Cu is rapidly transferred to its transport protein ceruloplasmin, though a small fraction persists in a ternary (Cu2+-histidine-threonine) complex. There is likewise no necessity to postulate any active mechanism for Cu uptake into plant cells and the evidence suggests transport through the plant in the form of organic complexes which remain to be characterised (GRAHAM 1979). It has frequently been noted in studies of clones of A. tenuis that the Cu requirement for optimal growth is higher for Cu-tolerant than for Cu-susceptible (1971) clones.…”
Section: A) Mechanisms For the Exclusion Or Diminution Of Uptake Of Cmentioning
confidence: 99%
“…Several authors have used Strategy I plants for studies on mineral ions in the xylem sap and their possible relationship with the phenomenon of metal complexation and transport from roots to shoots (Tiffin 1967;Graham 1979;White et al 1981b). Translocation of nutrients in the xylem sap varies with the plant species.…”
mentioning
confidence: 99%